2015
DOI: 10.1111/irv.12310
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers' willingness to work during an influenza pandemic: a systematic review and meta‐analysis

Abstract: To estimate the proportion of healthcare workers (HCWs) willing to work during an influenza pandemic and identify associated risk factors, we undertook a systematic review and meta-analysis compliant with PRISMA guidance. Databases and grey literature were searched to April 2013, and records were screened against protocol eligibility criteria. Data extraction and risk of bias assessments were undertaken using a piloted form. Random-effects meta-analyses estimated (i) pooled proportion of HCWs willing to work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
201
6
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(230 citation statements)
references
References 68 publications
18
201
6
5
Order By: Relevance
“…19 The reason nurses with children did not want to volunteer could be related to this. 20 In this situation, the only strength was support from friends and family. Participants were close to each other and even expressed support at the time owing to comradery.…”
Section: Discussionmentioning
confidence: 99%
“…19 The reason nurses with children did not want to volunteer could be related to this. 20 In this situation, the only strength was support from friends and family. Participants were close to each other and even expressed support at the time owing to comradery.…”
Section: Discussionmentioning
confidence: 99%
“…Experience in our hospitals in the past few weeks, although anecdotal, is concordant with these reports. The disruption of routine clinical practice, the sense of loss of control and the subsequent fear of potential destabilization of the health services, has provoked 'overflowing' anxiety and depression among healthcare professionals, a feature which is not uncommon of epidemics (9,11). Depression is associated with poor medication adherence (12) which may increase morbidity among older healthcare professionals with coexisting medical conditions.…”
Section: Psychological Impact On Healthcare Professionalsmentioning
confidence: 99%
“…Despite their professional duties, 28% of hospital health care employees surveyed at a German university hospital considered it acceptable not to report for work during a viral pandemic [19]. Similarly, in a qualitative study that explored the views of 64 HCWs in the UK about working during an influenza pandemic, the perceived factors related to unwillingness to work included child care responsibilities, concern about the wellbeing of family members, lack of information about the risks of infection, no clear role during the crisis, and lack of trust in the health organization [20][21][22]. Our results were consistent with these previous reports [19,20,22], as we found that previously caring for patients with same disease and good perception of infection control measures were associated with a lesser tendency to adopt an escape behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a qualitative study that explored the views of 64 HCWs in the UK about working during an influenza pandemic, the perceived factors related to unwillingness to work included child care responsibilities, concern about the wellbeing of family members, lack of information about the risks of infection, no clear role during the crisis, and lack of trust in the health organization [20][21][22]. Our results were consistent with these previous reports [19,20,22], as we found that previously caring for patients with same disease and good perception of infection control measures were associated with a lesser tendency to adopt an escape behavior. On the other hand, the more worried the HWC was for self and family members, and the more fearful he/she was about vaccination side effects or being assigned to care for an infected patient, the more he/she was likely to avoid work and reschedule work shifts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation